Academic Anxiety Among College Students Reviewed From Gender, Age, and Academic Year Perspective - Elin Maulida Rahmawati; Ahman; Setiawati; Zeed Hamdy Rukman; Dina Dwi Rahayu (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
Academic anxiety is a form of emotional response triggered by unpleasant situations such as fear, anxiety, tension, and worry caused by the academic process. This study aims to describe academic anxiety in college students in terms of gender, age, and academic year. Adopting a positive paradigm, this study used a quantitative approach with a survey design. The research population includes active students of BK FIP UPI class of 2019-2022 academic year 2022/2023. The research sample was 348 taken using a non-probability sampling technique and saturated sample type. The results of the study can be concluded as follows: (1) In general, the tendency of students' academic anxiety is in the “moderate” category. (2) Female students show a higher level of academic anxiety. (3) Older students tend to have the highest level of academic anxiety. (4) Final year students have the highest level of academic anxiety. This research can help higher education counseling centers to provide guidance and counseling services to students who experience academic anxiety in facing the challenges of studying. Keywords: anxiety, academic anxiety, college student